At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To simplify the expression [tex]\(\frac{x^3 y^{\frac{1}{2}} z^5}{x^{-\frac{4}{3}}\left(y^2 z\right)^5}\)[/tex], we need to break it down step-by-step and use the laws of exponents.
Given expression:
[tex]\[ \frac{x^3 y^{\frac{1}{2}} z^5}{x^{-\frac{4}{3}}\left(y^2 z\right)^5} \][/tex]
First, let's simplify the denominator:
[tex]\[ x^{-\frac{4}{3}} \left(y^2 z\right)^5 \][/tex]
Using the power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex], we can expand [tex]\(\left(y^2 z\right)^5\)[/tex]:
[tex]\[ \left(y^2 z\right)^5 = (y^2)^5 \cdot z^5 = y^{2 \cdot 5} \cdot z^5 = y^{10} \cdot z^5 \][/tex]
So now the denominator is:
[tex]\[ x^{-\frac{4}{3}} y^{10} z^5 \][/tex]
Now the expression becomes:
[tex]\[ \frac{x^3 y^{\frac{1}{2}} z^5}{x^{-\frac{4}{3}} y^{10} z^5} \][/tex]
Next, we can separate the variables:
[tex]\[ \frac{x^3}{x^{-\frac{4}{3}}} \cdot \frac{y^{\frac{1}{2}}}{y^{10}} \cdot \frac{z^5}{z^5} \][/tex]
Simplifying each fraction individually:
1. Simplify the [tex]\(x\)[/tex] terms:
[tex]\[ \frac{x^3}{x^{-\frac{4}{3}}} = x^{3 - \left(-\frac{4}{3}\right)} = x^{3 + \frac{4}{3}} = x^{\frac{9}{3} + \frac{4}{3}} = x^{\frac{13}{3}} \][/tex]
2. Simplify the [tex]\(y\)[/tex] terms:
[tex]\[ \frac{y^{\frac{1}{2}}}{y^{10}} = y^{\frac{1}{2} - 10} = y^{\frac{1}{2} - \frac{20}{2}} = y^{-\frac{19}{2}} \][/tex]
3. Simplify the [tex]\(z\)[/tex] terms:
[tex]\[ \frac{z^5}{z^5} = z^{5 - 5} = z^0 = 1 \][/tex]
So combining all the simplified parts together, we get:
[tex]\[ x^{\frac{13}{3}} \cdot y^{-\frac{19}{2}} \cdot 1 = x^{\frac{13}{3}} y^{-\frac{19}{2}} \][/tex]
Therefore, the expression equivalent to the given expression is:
[tex]\[ x^{\frac{13}{3}} y^{-\frac{19}{2}} \][/tex]
The correct answer is:
A) [tex]\(x^{\frac{13}{3}} y^{-\frac{19}{2}}\)[/tex]
Given expression:
[tex]\[ \frac{x^3 y^{\frac{1}{2}} z^5}{x^{-\frac{4}{3}}\left(y^2 z\right)^5} \][/tex]
First, let's simplify the denominator:
[tex]\[ x^{-\frac{4}{3}} \left(y^2 z\right)^5 \][/tex]
Using the power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex], we can expand [tex]\(\left(y^2 z\right)^5\)[/tex]:
[tex]\[ \left(y^2 z\right)^5 = (y^2)^5 \cdot z^5 = y^{2 \cdot 5} \cdot z^5 = y^{10} \cdot z^5 \][/tex]
So now the denominator is:
[tex]\[ x^{-\frac{4}{3}} y^{10} z^5 \][/tex]
Now the expression becomes:
[tex]\[ \frac{x^3 y^{\frac{1}{2}} z^5}{x^{-\frac{4}{3}} y^{10} z^5} \][/tex]
Next, we can separate the variables:
[tex]\[ \frac{x^3}{x^{-\frac{4}{3}}} \cdot \frac{y^{\frac{1}{2}}}{y^{10}} \cdot \frac{z^5}{z^5} \][/tex]
Simplifying each fraction individually:
1. Simplify the [tex]\(x\)[/tex] terms:
[tex]\[ \frac{x^3}{x^{-\frac{4}{3}}} = x^{3 - \left(-\frac{4}{3}\right)} = x^{3 + \frac{4}{3}} = x^{\frac{9}{3} + \frac{4}{3}} = x^{\frac{13}{3}} \][/tex]
2. Simplify the [tex]\(y\)[/tex] terms:
[tex]\[ \frac{y^{\frac{1}{2}}}{y^{10}} = y^{\frac{1}{2} - 10} = y^{\frac{1}{2} - \frac{20}{2}} = y^{-\frac{19}{2}} \][/tex]
3. Simplify the [tex]\(z\)[/tex] terms:
[tex]\[ \frac{z^5}{z^5} = z^{5 - 5} = z^0 = 1 \][/tex]
So combining all the simplified parts together, we get:
[tex]\[ x^{\frac{13}{3}} \cdot y^{-\frac{19}{2}} \cdot 1 = x^{\frac{13}{3}} y^{-\frac{19}{2}} \][/tex]
Therefore, the expression equivalent to the given expression is:
[tex]\[ x^{\frac{13}{3}} y^{-\frac{19}{2}} \][/tex]
The correct answer is:
A) [tex]\(x^{\frac{13}{3}} y^{-\frac{19}{2}}\)[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.